Deposition of Nano-Crystalline Fluor-hydroxyapatite Coatingson Titanium Substrates via Sol-Gel Method: Deposition of nano-crystalline fluorhydroxyapatite coatings on titanium substrates - Sedigheh Joughehdoust,; Aliasghar Behnamghader,; Abdollah Afshar, (Iranian Journal of Pharmaceutical Sciences, 2008)
In this investigation, fluor-hydroxyapatite (FHA) film was deposited on a titanium substrate by sol-gel method. Triethyl phosphite, ammonium fluoride and calcium nitrate in ethanol solutions were used respectively as P, F and Ca precursors.Typical apatite structures were obtained for all coatings after dipping and subsequent heat treatment at 550, 700 and 800 ºC, the coating layers were investigated with X-ray diffraction, Fourier transform infra-red and Scanning electron microscopy spectroscopy. Based on the results obtained from X-ray diffraction, the coatings heated at 550 ºC were composed of hydroxyapatite (HA) and fluorapatite (FA). Rutile (TiO2)phase was also found in the coatings heated at higher temperature. In addition, the formation of fluor-hydroxyapatite was confirmed by FT-IR results. SEM studies showed the samples heat treated at 550 ºC and 700 ºC have almost the same morphology. It seems the coating of samples heat treated in 800 ºC was more homogenous and smooth without any considerable porosity.